Handbook of primary care procedures. (Philadelphia, Pennsylvania : Lippincott Williams & Wilkins, 2003)
"Get expert help for more than 200 procedures, from injections and cyst removal to fracture immobilization and suturing of lacerations. Includes comprehensive coverage in a quick-reference format, CPT billing codes, indications and contraindications, preprocedure patient preparation, equipment you'll need and how to prepare it, essential procedural steps, postprocedure patient teaching, potential complications, special considerations, and documentation tips." "Packed with the features you need most: clinical tips on proper techniques, care points, and modifications for special patients; informed consent icons that tell you when informed consent is essential; collaboration icons that remind you of pertinent referrals or consultations; more than 200 illustrations and photos that clarify techniques, uses of equipment, and more; English-Spanish translations for common medical words and phrases to facilitate clear communication; and 12-lead ECG interpretation guide that enhances your ability to analyze and correctly identify and treat all major arrhythmias."--Jacket
Procedures (in alphabetical order) -- A. Medical English-Spanish translations -- B. Obtaining informed consent -- C. 12-lead ECG interpretation.
Includes bibliographical references and index.
Keywords: PRIMARY HEALTH CARE